The role of oxysterols in vascular ageing. (19th January 2016) - Gargiulo, Simona; Gamba, Paola; Testa, Gabriella; Leonarduzzi, Gabriella; Poli, Giuseppe
Abstract : Oxysterol‐driven anticipation and/or amplification of the main features of ageing blood vessels. Abstract: The ageing endothelium progressively loses its remarkable and crucial ability to maintain homeostasis of the vasculature, as it acquires a proinflammatory phenotype. Cellular and structural changes gradually accumulate in the blood vessels, and markedly in artery walls. Most changes in aged arteries are comparable to those occurring during the atherogenic process, the latter being more marked: pro‐oxidant and proinflammatory molecules, mainly deriving from or triggered by oxidized low density lipoproteins (oxLDLs), are undoubtedly a major driving force of this process. Oxysterols, quantitatively relevant components of oxLDLs, are likely candidate molecules in the pathogenesis of vascular ageing, because of their marked pro‐oxidant, proinflammatory and proapoptotic properties. An increasing bulk of experimental data point to the contribution of a variety of oxysterols of pathophysiological interest, also in the age‐related genesis of endothelium dysfunction, intimal thickening due to lipid accumulation, and smooth muscle cell migration and arterial stiffness due to increasing collagen deposition and calcification. This review provides an updated analysis of the molecular mechanisms whereby oxysterols accumulating in the wall of ageing blood vessels may 'activate' endothelial and monocytic cells, through expression of an inflammatory phenotype, and 'convince' smooth muscle cells to proliferate, migrate and, above all, to act as fibroblast‐like cells.